Response of tomato growth and number of mycorrhizal spores applied with biochar on saline soil - Vitha Vitha; Fachrul Busri; Gina Nurawalia; Nadia Nadia; Greis Greis (Anjoro: International Journal of Agriculture and Business, 2025)
High evaporation in coastal areas leads to salt accumulation in the soil, elevating soil salinity. Tomato plants (Lycopersicum esculentum L.) are one of the ideal plants for evaluating saline soil amelioration strategies. Inadequate saline soil treatment is an obstacle for farmers in developing their agricultural practices. Therefore, saline soil remediation using biochar was conducted to reduce soil salinity levels. The study was conducted using a non- factorial randomized block design (RBD) with 4 replications and 4 treatments, namely B0 (control), B1 (50 grams of biochar), B2 (100 grams of biochar), and B3 (150 grams of biochar) with observation parameters of plant height, number of leaves, stem diameter, and number of arbuscular mycorrhizal (AMF) spores. The results of this study showed that biochar had no significant effect on plant growth and the number of spores in tomato roots. Therefore, based on the study's results, the use of biochar in tomato growing media did not significantly affect plant growth parameters or the number of AMF spores in the growing media. Various factors, including environmental conditions and interactions between the growing media and host plants, may influence this. Recommended that further research be conducted on the process of producing biochar using anaerobic pyrolysis or closed pyrolysis methods. This is important because anaerobic combustion can produce more stable biochar.